Analisis Risiko Bahaya dengan Metode Hazard Identification, Risk Assessment and Determining Control (HIRADC) pada Industri Kecil Mebel (Studi Kasus : Mebel Homedecore, Driyorejo, Gresik) - Safitri, Berliana; Arismawati, Paramaditya; Wahyuni, Ayu Endah (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The HomeDecore furniture industry is a small industry sector that focuses on manufacturing furniture products from wood-based materials. The production process in this furniture involves the process of cutting wood, smoothing wood and the assembly process. This process poses a risk of hazards that result in accidents at work. Broadly speaking, work accidents are caused by two factors, namely human actions that do not meet work safety (unsafe action) and unsafe conditions. The purpose of this research is to identify hazard risks and determine control measures to reduce the risk of work accidents. This research was conducted using the Hazard Identification, Risk Assessment And Determining Control (HIRADC) method to identify hazards, analyze risks and determine risk control measures to ensure the safety of workers. With this research, hopefully it can help reduce the risk of hazards. Based on the results of this study, several recommendations are determined according to the hazard control hierarchy by carrying out control measures such as elimination, substitution, engineering control, administrative and PPE (Personal Protective Equipment.